Sleeping quality, sleeping habits, and their association with BMI in children in southern China - Huang, Chuican; Lei, Yue; Wu, Weijia; Luo, Qing; Cao, Wenting; Xie, Junwei; Li, Hongai; Fan, Lichun (Frontiers in Pediatrics, 2025)
ObjectivesThis study analyzes the effects of sleep quality along with sleep duration and bedtime on BMI in children aged 3–12 years and explores their role in the occurrence and development of obesity in children.MethodsThis study conducted a cross-section study on children in 18 cities and counties of Hainan Province. The Children's Sleep Habits Questionnaire (CSHQ), along with a parents-report children's features survey, was used to assess children's sleep quality and habits, among other factors.ResultsThe multivariable analysis results showed that bedtime was positively correlated with childhood overweight or obesity. However, the relationship between the outcome and sleep duration in children remains uncertain. The results of the additive interaction model indicated that sleep duration between 9 and 11 h or 11 h and above, combined with poor sleep quality or earlier bedtime (before 21:00), served as protective factors against children's overweight or obesity. Conversely, children with adequate sleep duration but later bedtime had a higher risk of being overweight or obese [OR (odds ratio): 1.214, 95% CI: 1.069–1.379]. Children with sleep duration less than 9 h, regardless of bedtime, had an increased risk of adverse outcomes (OR: 1.394, 95% CI: 1.022–1.901; OR: 1.268, 95% CI: 1.039–1.548).ConclusionShort sleep duration (<9 h) and late bedtime (>22:00) independently and synergistically increase obesity risk, while adherence to recommended sleep patterns (9–11 h, bedtime before 21:00) offers protection. Non-linear analyses confirm a heightened obesity risk below 9 h of sleep, with partial attenuation beyond 11 h. Poor sleep quality paradoxically associates with lower obesity risk.